Is it possible to change the human voice? - analysis of the medical review on the example of people facing gender dysphoria - Branewska, Justyna; Kołodziejczyk, Kacper; Ostrowska, Barbara; Hop, Izabela; Matysek, Mikołaj; Olszanicka, Anna; Imioło, Jan; Maciąg, Anna; Niemiec, Rafał; Galas, Adam (Journal of Education, Health and Sport, 2023)
Introduction The term gender dysphoria has been known to humanity for a long time. Transsexuality has many definitions, but each of them leads to the same conclusions. It is a lack of acceptance of one's own biological sex, the one indicated by the anatomy and sex given to a newborn human. For these people, it is important that their appearance and tone of voice allow them to be recognized according to the gender they want to represent. This topic requires a multidisciplinary approach of specialists from various fields of medicine, such as: phoniatrics, otolaryngology, endocrinology, surgery and psychiatry. Purpose The aim of study is to review data on voice modification in both transgender men and transgender women. The possibilities that medicine offers to people who want to change the tone, quality and pitch of their voice will be emphasized. Methods A systematic review and meta-analysis of the literature was performed using the PubMed, Cochrane, Embase, Medline, and Science Direct databases. Results Changing the voice of transgender people is essential for self-acceptance and improves the quality of life of such people. Mental health problems such as depression and anxiety have been found to be significantly less after treatment has been implemented in these people's lives. Conclusions Medicine offers many solutions, from conservative to invasive. Over the years, therapies have been developed that combine many medical fields, and these often bring the expected results. People who decide to undergo surgery must be aware that the results may not always be as expected or that complications may occur.